On Translating Metaphor - Alvarez, Antonia (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractOne of the main difficulties a literary translator has to face is metaphorical language. In view of its importance and frequency it constitutes an essential element in translation process, but it has received little attention by translation theorists, perhaps because of the obstacles to reach some kind of theory of metaphor translation. That's why we'll try to make some generalizations on translating metaphor, using as a frame to develop our analysis a text by Angela Carter, since metaphor is a true, recurrent medium for her artistic vision of literature. As most critics say, in her baroque use of imagery, metaphor is at the heart of Carter's creative process and has a special claim for the reader's attention.